Relationships between motor effects and after-discharges induced by electrical stimulation of amygdala and hippocampus (Revista Española de Fisiología, 1974)
Relationships Between Motor Effects and After-discharges Induced by Eléctrica! Stimulation of Amygdala and Hippocampus. Rev. esp. Fisiol., 30, 269-272. 1974.The amygdala and the hippocampus of 35 cats have been electrically stimulated in order to study the relationships between motor responses and electrical after- discharges. The results were as follows: a) the hippocampus showed a low percentage of motor responses without after-discharges, while it showed high percentages of after- discharges without motor responses; and b) the amygdala (specially the amygdala centralis) showed the opposite phenomenon: high level of motor reponses without after-discharges, but only one after-discharge without induced motor effect.